An Interactive 3-D Audio System With Loudspeakers - Song, Myung-Suk; Zhang, Cha; Florencio, Dinei; Kang, Hong-Goo (IEEE Transactions on Multimedia, 2011)
Traditional 3-D audio systems using two loudspeakers often have a limited sweet spot and may suffer from poor performance in reverberant environments. This paper presents a novel binaural 3-D audio system that actively combines head tracking and room modeling into 3-D audio synthesis. The user’s head position and orientation are first tracked by a webcam-based 3-D head tracker. The system then improves its robustness to head movement and strong early reflections by incorporating the tracking information and an explicit room model into the binaural synthesis and crosstalk cancellation process. Sensitivity analysis on the room model shows that the method is reasonably robust to modeling errors. Subjective listening tests confirm that the proposed 3-D audio system significantly improves the users’ perception and ability for localization.